PUPALIA LAPPACEA JUSS [L]: A REVIEW OF PHYTOCHEMISTRY AND THERAPEUTIC APPLICATION - NAIDU, PRASAD P; Rajesh, Bandi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Pupalia lappacea containing diverse group of phytochemicals, namely; 1- docosa-nol, stearic acid, stigamasterol, Î²-sitosterol, saropeptate (N-benzoyl-L-Phyenylalaninol acetate), Î²-sitosterol-3-0-Dâ€“glucopyranoside, Stigmasterol-3-0-Î²-D-glucopyra-noside and 20 â€“ hydroxylecdysone are known to have potential therapeutic application. In folklore and ayurvedic medicine, it has been used to treat wounds, bone fractures, boils, cough, toothache, fever and malaria, diarrhea, urethra pain, leucorrhoea and many other disorders. Invivo Clinical studies showed that ethanolic extracts of Pupalia lappacea have anticioceptive, antipyretic, anti-inflammatory properties. Invitro experimental studies had revealed that Pupalia lappacea exhibits antioxidant and anticancer properties. Clinical studies should be initiated to generate novel drugs and to prove its immense therapeutic efficacy as a potent phytomedicine. Â Key words: Pupalia lappacea, Anticancer, Anticioceptive, Phytomedicine.